Multiple methods of public engagement: Disaggregating socio-spatial data for environmental planning in western Washington, USA. (15th December 2017) - McLain, Rebecca J.; Banis, David; Todd, Alexa; Cerveny, Lee K.
Highlights: The effectiveness of participatory GIS approaches at engaging different publics was explored. Online surveys engaged urbanites; community workshops engaged rural residents. Urban and rural residents went to similar places but engaged in different activities. Use of multiple data collection methods will broaden public engagement. Mapping behavior studies are needed to improve understandings of PPGIS data quality.